The Multiple Sclerosis Treatment Optimization Program - Annette Langer‐Gould (Wiley, 2021)
Abstract Objective To design and implement a health system level intervention to reduce escalating multiple sclerosis (MS) disease modifying treatment (DMT) expenditures and improve outcomes. Methods We conducted stakeholder meetings, reviewed pharmacy utilization data, and abstracted information in subsets of persons with MS (pwMS) from the electronic health record to identify gaps in, and barriers to improving, quality, and affordability of MS care in Kaiser Permanente Southern California. These results informed the development and implementation of the MS Treatment Optimization Program (MSTOP). Results The two main gaps identified were under‐prescribing of highly effective DMTs (HET, 4.9%) and the preferred formulary DMT (20.9%) among DMT‐treated pwMS. The main barriers identified were prescribers’ fear of rare but serious HET side effects, lack of MS‐specific and health systems science knowledge, Pharma influence, evidence gaps, formulary decisions‐based solely on costs, and multidirectional mistrust between neurologists, practice leaders, and health plan pharmacists. To overcome these barriers MSTOP developed four strategies: (1) risk‐stratified treatment algorithm to increase use of HETs; (2) an expert‐led ethical, cost‐sensitive, risk‐stratified, preferred formulary; (3) proactive counter‐launch campaigns to minimize uptake of new, low‐value DMTs; and (4) discontinuation of ineffective DMTs in progressive, non‐relapsing MS. The multicomponent MSTOP was implemented through education, training, and expanding access to MS‐trained providers, audit and feedback, and continual evidence reviews. Interpretation The causes of wasteful spending on MS DMTs are complex and require multiple strategies to resolve. We provide herein granular details of how we designed and implemented our health system intervention to facilitate its adaption to other settings and conditions.